Jurnalisme Online Sebagai Komunikasi Pariwisata - Nanang Haroni; Zakaria L. Sukirno (Diploma Travel Business, Faculty of Social and Political Science, Jember University, 2019)
Abstract An activity of collecting, preparing, writing, editing, and delivering or widespreading news to the public through certain media channels is considered as journalistic. Since the innovation of public internet, journalism met a new challenge. Racing along the dynamic speed, some journalism principles as verification has been entering a redefinition phase. The other challenge is the rise of specified content that places journalism to the smaller sphere – but more in depth – such as literature, role, entertainment, fashion, and tourist journalism.. As an industry, tourist attraction wouldn’t be popular in the eyes of public and target tourist if it’s not socialized and promoted effectively and extensively. As well as using marketing communication strategy and practices, tourist destination can be communicated by news. How does a good news writing technique for tourist journalism apply? This article proposes a tourist journalism writing model that is able to produce and interesting writing outcome. This tourist journalism model is trying to develop 5W 1 H pattern (what, who, when, where, why, and how) by modifying the content pattern that has been tailored with the purpose of tourism socialization. Keywords: journalism, online, tourism, 5W 1H.